A Product Layout Design For Finished Goods Warehouse Of Instant Noodle Industry Using Systematic Layout Planning (SLP) Method - Asep Hermawan; Dedy Setyo Oetomo (Universitas Insan Cendekia Mandiri, 2026)
Warehouse layout optimization in the food manufacturing industry remains a critical yet underexplored challenge, particularly for multi-product operations with heterogeneous storage requirements and high-throughput demands. Previous studies have predominantly focused on single-criterion evaluations or general industrial settings, leaving a notable gap in the application of comprehensive, multi-criteria Systematic Layout Planning (SLP) frameworks to finished goods warehouses in the food sector. This study addresses that gap by designing an optimal product layout for a finished goods warehouse in an instant noodle manufacturing facility with an annual production capacity of 20 million units. The SLP method was implemented through six structured phases: activity relationship analysis, space requirements determination, relationship and space diagram construction, alternative layout generation, and weighted multi-criteria quantitative evaluation. Three layout alternatives were systematically assessed using criteria encompassing material handling efficiency, space utilization, operational flexibility, and implementation cost. The U-shaped layout emerged as the optimal design, attaining the highest weighted evaluation score and demonstrating substantial reductions in material handling distance and operational cost relative to conventional linear configurations. The findings confirm that the SLP method provides a robust and replicable framework for warehouse layout optimization in multi-product food manufacturing environments, offering actionable guidance for facility planners confronting analogous operational constraints.